PEMANFAATAN CANGKANG KEONG EMAS SEBAGAI BAHAN ALTERNATIF PEMBUATAN PAPAN PARTIKEL (Studi Kasus Dengan Penambahan Serbuk Kayu Mahoni Dan Randu) - , GILANG KUMORO DEWOJATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Demand for wood as the primary building material increasingly difficult to obtain, resulting in rising prices and materials needed replacement started. Economical replacement material that can replace wooden planks and one of them is particle board. The research was conducted because many golden snail shell wasted in Embung Rowo Jombor in Central Java, Village Jimbung, Kali Kotes Subdistrict, Klaten. The majority of the population are work as farmers of their livelihood fish by using the results obtained from the dam Rowo Jombor. One way to search for golden snail that they take advantage of snails into slugs broil foods that we often encounter in the market. The processing of the golden snail waste conch large enough numbers. So with this research, I hope to provide solutions substitutes wood waste and solve the problems golden snail conch at Rowo Jombor.